Floristical notes from Valle del Paular (Madrid, Spain), II - Fernández-González, Federico (Lazaroa, 2014)
Some taxa of regional chorological or ecological interest collected in Valle del Paular (Madrid, Spain) are briefly commented. A determination key for the Iberian species of the genus Elatine L. is proposed.